2023
DOI: 10.3126/irjmmc.v4i1.51863
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Research Landscape: A Guide to the Selection of the Right Research Design

Abstract: Research design, which is a plan or framework for conducting an investigatory study, engrosses the ways for collecting and analyzing data. It is circumspectly planned in advance as it influences the quality and validity of the research outcomes. There are broadly three sorts of research designs, namely quantitative, qualitative and mixed methods research designs. Quantitative research designs involve the collection and analysis of numerical data, qualitative research designs include the collection and analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The analysis of the various conceptualisation of mixed methods by most authors and scholars revealed that mixed methods is situated within the context of both research designs and types of research, although it was not expressly listed among the types of research (Creswell & Plano-Clark, 2007Tashakkori & Teddlie, 2010;Ary et al, 2010;Kumar, 2008;Cohen et al, 2018;Tobi & Kampen, 2018;Asenahabi, 2019;Neelam, 2020;Sato, 2022;Adeniji et al, 2022;Egunjobi, 2022;Love et al, 2022;Igiebor & Okonmah, 2022;Taherdoost, 2022;Abubakar & Ahmad, 2023: Hampson & McKinley, 2023Otieno & Owino, 2023;Hagan, Spillane & Curran, 2023;Sharma et al, 2023). However, there are authors on research methodologies who classified mixed methods as a research design with designs such as convergent parallel, exploratory, explanatory, sequential, transformative, and embedded (Tashakkori & Teddlie, 2003;Abosede & Onanuga, 2016;Creswell & Creswell, 2017;Creswell, 2018;Tobi & Kampen, 2018;Asenahabi, 2019;Dawadi et al, 2021;Adeniji et al, 2022;Igiebor & Okonmah, 2022;Otieno & Owino, 2023;Sharma et al, 2023).…”
Section: Findings Summary Of Findings: Synthesis For Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the various conceptualisation of mixed methods by most authors and scholars revealed that mixed methods is situated within the context of both research designs and types of research, although it was not expressly listed among the types of research (Creswell & Plano-Clark, 2007Tashakkori & Teddlie, 2010;Ary et al, 2010;Kumar, 2008;Cohen et al, 2018;Tobi & Kampen, 2018;Asenahabi, 2019;Neelam, 2020;Sato, 2022;Adeniji et al, 2022;Egunjobi, 2022;Love et al, 2022;Igiebor & Okonmah, 2022;Taherdoost, 2022;Abubakar & Ahmad, 2023: Hampson & McKinley, 2023Otieno & Owino, 2023;Hagan, Spillane & Curran, 2023;Sharma et al, 2023). However, there are authors on research methodologies who classified mixed methods as a research design with designs such as convergent parallel, exploratory, explanatory, sequential, transformative, and embedded (Tashakkori & Teddlie, 2003;Abosede & Onanuga, 2016;Creswell & Creswell, 2017;Creswell, 2018;Tobi & Kampen, 2018;Asenahabi, 2019;Dawadi et al, 2021;Adeniji et al, 2022;Igiebor & Okonmah, 2022;Otieno & Owino, 2023;Sharma et al, 2023).…”
Section: Findings Summary Of Findings: Synthesis For Discoursementioning
confidence: 99%
“…Also, some authors view mixed methods from the point of a research approach or research strategy that can be used for any type of research (Johnson & Onwuegbuzie, 2004;Singh, 2011;Trochim et al, 2015;Gliner et al, 2017;Cohen et al, 2018;Tobi & Kampen, 2018;Dawadi et al, 2021;Adeniji et al, 2022;Love et al, 2022;Mattar & Ramos, 2022;Taherdoost, 2022;Igiebor & Okonmah, 2022;Sato, 2022;Pashaie et al, 2023;Sharma et al, 2023). Some other authors described mixed methods as a research methodology (Dawadi et al, 2021;Mattar & Ramos, 2022;Igiebor & Okonmah, 2022;Pashaie et al, 2023) (See Table 3).…”
Section: Findings Summary Of Findings: Synthesis For Discoursementioning
confidence: 99%